2012
DOI: 10.1186/1471-2431-12-132
|View full text |Cite
|
Sign up to set email alerts
|

Pain and stress assessment after retinopathy of prematurity screening examination: Indirect ophthalmoscopy versus digital retinal imaging

Abstract: BackgroundIncreasingly, neonatal clinics seek to minimize painful experiences and stress for premature infants. Fundoscopy performed with a binocular indirect ophthalmoscope is the reference examination technique for screening of retinopathy of prematurity (ROP), and it is associated with pain and stress. Wide-field digital retinal imaging is a recent technique that should be evaluated for minimizing infant pain and stress.MethodsThe purpose of the study was to assess and compare the impact of using a binocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 24 publications
0
46
1
Order By: Relevance
“…Temporary levels of distress occur during both the clinical examination and during retinal imaging. 32,33 It is possible that examiners over-called zone I in cases where they made this determination while the infant or the infant’s eye was moving during the examination. On the other hand, the reader of the digital retinal image was able to apply a standard definition of zone I on the motionless retinal image with precision.…”
Section: Discussionmentioning
confidence: 99%
“…Temporary levels of distress occur during both the clinical examination and during retinal imaging. 32,33 It is possible that examiners over-called zone I in cases where they made this determination while the infant or the infant’s eye was moving during the examination. On the other hand, the reader of the digital retinal image was able to apply a standard definition of zone I on the motionless retinal image with precision.…”
Section: Discussionmentioning
confidence: 99%
“…(12, 1517) Clinical findings that occur during ROP screening procedures highlight the fragility of extremely premature infants, their propensity to have apnea, bradycardia and hypoxia events, as well as the pain response and oculocardiac reflex invoked by ROP evaluation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that only 20–66% of infants screened for ROP will develop ROP [711] and an even smaller number (5–10%) will require treatment [7, 9, 10, 12], resulting in many infants being screened unnecessarily. Screening examinations are stressful for infants [13, 14], and are known to have adverse physiologic effects, including an increase in apnea events among screened infants. [15, 16] As such, there is a significant incentive to limit unnecessary screening examinations.…”
Section: Introductionmentioning
confidence: 99%